THE ROLE OF SOCIAL MEDIA IN INCREASING STUDENT LEARNING MOTIVATION IN THE DIGITAL AGE - Winda Fingki Andika, Winda Fingki (Proceeding International Seminar of Islamic Studies, 2023)
The existence of social media has changed how access to networked digital technology. To deal with increasingly sophisticated developments in science and technology and increasingly intense globalization. Learning motivation is very closely related to student behavior at school so that it can arouse and direct students to learn something new and worry that the tendency to use social media can have a positive or negative influence on student learning motivation and discipline. The purpose of this study was to determine the percentage of the role of the media social media in increasing the learning motivation of high school students. The research method is a quantitative descriptive method. The results of his research, namely your spare time opening social media accounts 76%, the impact of social media on students 71%, opening social media while studying 47% chose to play social media rather than study 57%, So it can be concluded that social media factors can affect student learning motivation approved by students with a percentage of 59.1%.